Shipboard Guardian: Sistem IoT untuk Pemantauan Suhu dan Kelembaban Ruangan Kelistrikan Kapal - Jumrianto, Jumrianto; Hariningrum, Rita; Purnamasari, Dewi; Rosyihin, Ashof (JURNAL BARTEK, 2026)
The electrical system on a ship is a critical area vulnerable to system failure and fire risks due to excessive temperature or humidity. This research aims to design and implement a remote temperature and humidity monitoring system called "Shipboard Guardian," based on Internet of Things (IoT) technology. This system design method utilizes a NodeMCU ESP8266 as the main microcontroller, processing data from the DHT11 sensor (to detect temperature and humidity) and controlling actuator components such as LEDs and buzzers. Data collected by the sensor is then sent in real time to the cloud via the Internet of Things.Cloud platform. Internet of Things serves as a visual interface (dashboard) that allows ship crew or shore operators to monitor the condition of the ship's electrical system through a smartphone or web application. Key features of this system include: (1) real-time monitoring of temperature and humidity of electrical rooms, (2) providing visual (LED) and audio (Buzzer) early warnings (alarms) when critical thresholds are exceeded, and (3) easy data access via the Internet of Things IoT platform. The implementation results show that "Shipboard Guardian" is able to detect and report temperature changes in the range of 0 oC to 50 oC and humidity of 20% to 90% with an accuracy level of 91.47. This system is expected to improve ship operational safety, minimize fire risks, and facilitate predictive maintenance on ship electrical systems.